Students Perceptions of Using TED Talks on Students Listening Comprehension in English Language Teaching - Sari, Cintami Velia; Sujarwati, Iis (Pedagonal : Jurnal Ilmiah Pendidikan, 2023)
For pupils to acquire English, listening skill is a key component. TED Talks have emerged as a useful resource for teaching students the importance of being able to listen. The aim of this research is to distinguish students’ perceptions of Using TED Talks on listening comprehension in English Language Teaching at The English Education Study Program of Bengkulu University. The research design was descriptive quantitative research which involved 33 undergraduate students from classes A of semester V in the 2022-2023 academic year. They are all enrolled in the English department at Bengkulu University. In this research, the data were collected using a questionnaire adopted from Izzah et al., (2020) through google forms consisting of 10 questions. Hereinafter, the data were analyzed using IBM SPSS (Statistical Package for the Social Science) 26.0 program. The result showed that students’ perceptions of using TED Talks on public speaking were positive perspectives. Since the students are already aware of TED Talks from a previous course, students generally had positive perceptions of using TED Talks to improve listening skills